Concept of stress dead zone in cracked plates: Theoretical, experimental, and computational studies. Issue 11 (15th February 2019) - Farahani, Behzad V.; Eslami, Shayan; de Melo, Francisco Q.; Tavares, Paulo J.; Moreira, Pedro M.G.P.
Abstract: This paper presents a study on stress dead zone implications and its characterization with uniaxial tensile testing on MT polycarbonate plate specimens. To obtain the experimental solution, digital image correlation (DIC) is used. Numerically, based on LEFM, the problem is solved using advanced discretization techniques, finite element, and meshless methods. Considering stress dead zone notion, it aims to determine alternative analytical solution of the SIF. Thus, the compliance method is adopted, which is associated with the specimen's dead zone region that does not involve the cracking resistance. Hence, LEFM formulations complying with strain energy release rate criterion are assumed. A proper comparison is made amongst results obtained from all theoretical, experimental, and numerical analyses. Furthermore, this work focuses on the variational fields' evaluation and, in particular, verification on the theoretical assumption of dead zone characteristics. The obtained results support adopted methodologies and are encouragingly robust and cost‐effective.